(untitled) (Dike - Rivista di Storia del Diritto Greco ed Ellenistico, 2018)
A law preserved in a quotation of Lysias, which states that the estates of orphans in fourth-century BCE Athens must be transformed into land, has been dismissed as spurious on the basis of contradictions with other laws. In recent years, however, although these contradictions have been shown to be more apparent than real, no scholar has reassessed the validity of the law in question. This paper argues that this law likely existed and that its intent was consistent with the way Athenian law tried to preserve the estates of its citizens. The interpretation that the law existed also brings additional clarity to the significance and meaning of passages regarding orphan estate management in Athenian oratorical sources